A lake sediment–based paleoecological reconstruction of late Holocene fire history and vegetation change in Great Basin National Park, Nevada, USA. (November 2021) - Cooper, Christopher S.; Porinchu, David F.; Reinemann, Scott A.; Mark, Bryan G.; DeGrand, James Q.
Abstract: Analyses of macroscopic charcoal, sediment geochemistry (%C, %N, C/N, δ 13 C, δ 15 N), and fossil pollen were conducted on a sediment core recovered from Stella Lake, Nevada, establishing a 2000 year record of fire history and vegetation change for the Great Basin. Charcoal accumulation rates (CHAR) indicate that fire activity, which was minimal from the beginning of the first millennium to AD 750, increased slightly at the onset of the Medieval Climate Anomaly (MCA). Observed changes in catchment vegetation were driven by hydroclimate variability during the early MCA. Two notable increases in CHAR, which occurred during the Little Ice Age (LIA), were identified as major fire events within the catchment. Increased C/N, enriched δ 15 N, and depleted δ 13 C values correspond with these events, providing additional evidence for the occurrence of catchment-scale fire events during the late fifteenth and late sixteenth centuries. Shifts in the vegetation community composition and structure accompanied these fires, with Pinus and Picea decreasing in relative abundance and Poaceae increasing in relative abundance following the fire events. During the LIA, the vegetation change and lacustrine geochemical response was most directly influenced by the occurrence of catchment-scale fires, not regional hydroclimate.